Compound cement and preparation method thereof

By adopting composite cement preparation methods with kaolin, slag powder, limestone powder, natural polymer and inorganic hydrates, the negative impact of existing cement retarder on the environment and unstable performance are solved, and environmental protection and Stable performance effect.

CN119462038APending Publication Date: 2025-02-18TAIHE YUHUA CEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411618147.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing cement retarder will have a negative impact on the environment during preparation and application, resulting in the release of VOCs of volatile organic compounds, and the fluctuations in the quality of raw materials in different batches lead to unstable performance of the final product.

Method used

The preparation method of compound cement is adopted, with kaolin, slag powder and limestone powder as the main components, and natural polymers (a mixture of polylactic acid and sodium alginate) and inorganic hydrates (such as calcium sulfate, calcium hydroxide, etc.) as compound. The ingredients are mixed and further adjusted during standstill and maturation to avoid the use of volatile organic compounds.

Benefits of technology

It achieves environmental protection effects, does not produce organic compounds to pollute the environment, has more stable performance and is not easy to degrade, and improves the environmental friendliness and durability of cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462038A_ABST
    Figure CN119462038A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement admixtures, and discloses compound cement and a preparation method thereof, and the compound cement is prepared by mixing a main component and a compound component. The components of the compound cement mainly comprise kaolin, slag powder and limestone powder which are natural minerals and wastes and have good environmental friendliness, the slag powder is a by-product generated in the steel smelting process and effectively reduces the influence of the wastes on the environment, and the used natural polymer is a mixture of polylactic acid and sodium alginate, so that the compound cement has the advantages of environmental protection and environmental protection. According to the present invention, the cement is derived from renewable resources, is natural and biodegradable, reduces the demand for synthesis of organic compounds so as to reduce the potential pollution of the organic compounds to the environment, uses deionized water as the solvent to ensure that no additional mineral substance or pollutant is mixed into the cement so as to improve the purity and the environmental protection characteristic of the cement, and has the characteristics of environmental protection and environmental protection; the finished compound cement has the beneficial effects that the finished compound cement has an environment-friendly effect and does not generate organic compounds to pollute the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement admixtures, in particular to a compound cement and a preparation method thereof. Background Art

[0002] Since the road construction process is complicated and takes a long time, in order to ensure the construction operation time and the quality of the base, cement retarders need to be applied during the road construction process. In current practical applications, cement retarders mainly include the following categories: monohydric alcohols such as methanol and ethanol, whose retarding time is not long and cannot meet the operational requirements of road construction; polyhydric alcohols such as ethylene glycol and propylene glycol, which have a good retarding effect, but the dosage is relatively high, generally 0.1-0.5%; sugars such as glucose and sucrose, which have both retarding and thickening effects; carboxylic acids such as citric acid, tartaric acid, salicylic acid, which have both retarding and inhibiting slump loss, but have a certain shrinkage effect on the early strength of concrete and mortar; hydroxyl / amino carboxylates such as sodium gluconate, whose dosage is generally between 0.02 and 0.15%, have good retarding effect, and also have water reducing effect, so it is not conducive to the later preparation of concrete; phosphate / phosphogypsum, which is generally used as an additive in the form of solid, and the addition amount is large, which is not conducive to transportation and cement production.

[0003] In order to solve the defects of the prior art, a high-performance composite cement retarder and a preparation method thereof are disclosed in publication number CN 111943563A. A silane coupling agent, an organic solvent and deionized water are added into a reactor to form a hydrolysis system of the silane coupling agent. The hydrolysis reaction of the silane coupling agent is carried out at a temperature of 40 to 120° C. to obtain a silane coupling agent hydrolyzate. A cationic surfactant, glucose, deionized water and the silane coupling agent hydrolyzate are added into a stirring kettle and stirred until a homogeneous phase is obtained. Thus, a high-performance cement retarder can be prepared. The high-performance cement retarder has an excellent retarding effect, a small dosage, a certain grinding aid effect on cement, and can improve the early and late strength of cement.

[0004] However, the glacial acetic acid and organic solvents: methanol and ethanol in the formula will have a negative impact on the environment during the preparation and application process, and release volatile organic compounds (VOCs). At the same time, different batches of raw materials will have quality fluctuations, especially the functional ingredients of surfactants and silane coupling agents, which will cause degradation or inconsistency of the performance of the final product. Summary of the invention

[0005] Technical issues solved:

[0006] In view of the deficiencies in the prior art, the present invention provides a compound cement and a preparation method thereof. The finished compound cement has the advantages of environmental protection, will not produce organic compounds to pollute the environment, has more stable performance and will not be easily degraded, thereby solving the problems of the above-mentioned technologies.

[0007] Technical solution:

[0008] To achieve the above object, the present invention provides the following technical solution: a composite cement, wherein the composite cement is prepared by mixing a main component and a composite component, wherein the main component is:

[0009] Kaolin 15%-30%;

[0010] Slag powder 20%-40%;

[0011] Limestone powder 10%-20%;

[0012] The compound ingredients are:

[0013] Natural polymer 5%-10%;

[0014] Inorganic hydrate 5%-20%;

[0015] The rest is deionized water;

[0016] The natural polymer is prepared by mixing polylactic acid and sodium alginate, the mass ratio of the polylactic acid and sodium alginate is 1:1, and the inorganic hydrate is prepared by mixing one or two of calcium sulfate, calcium hydroxide, calcium chloride and aluminum sulfate.

[0017] Preferably, the cement is prepared by mixing a main component and a compound component, wherein the main component is: 30% kaolin; 40% slag powder; 10% limestone powder; the compound component is: 5% natural polymer; 5% inorganic hydrate; and 10% deionized water.

[0018] Preferably, the cement is prepared by mixing a main component and a compound component, wherein the main component is: 15% kaolin; 20% slag powder; 20% limestone powder; the compound component is: 10% natural polymer; 20% inorganic hydrate; and 15% ion water.

[0019] Preferably, the cement is prepared by mixing a main component and a compound component, wherein the main component is: 20% kaolin; 35% slag powder; 15% limestone powder; the compound component is: 5% natural polymer; 15% inorganic hydrate; and 10% deionized water.

[0020] A method for preparing composite cement, the method comprising the following steps:

[0021] Step 1: prepare the required main components: kaolin, slag powder and limestone powder, polylactic acid, sodium alginate, inorganic hydrate, and select calcium sulfate, calcium hydroxide, calcium chloride or aluminum sulfate as needed;

[0022] Step 2: Mixing natural polymers: Mix polylactic acid and sodium alginate in a mass ratio of 1:1, and stir evenly until a uniform natural polymer solution is formed;

[0023] Step 3, preparing inorganic hydrate: selecting corresponding inorganic hydrate according to the formula: calcium sulfate, calcium hydroxide, calcium chloride, aluminum sulfate; mixing the selected inorganic hydrate with deionized water, stirring evenly until completely dissolved;

[0024] Step 4: Mix the main ingredients: In a mixing container, add kaolin, slag powder and limestone powder according to the proportion and stir well;

[0025] Step 5. Add compounding ingredients: Add the natural polymer solution prepared in step 2 and the inorganic hydrate solution prepared in step 3 to the main component mixture in proportion, continue stirring to ensure that all ingredients are evenly mixed, and add water to adjust: according to the desired final cement slurry consistency, add an appropriate amount of deionized water and stir evenly until the desired fluidity is achieved.

[0026] Step 6. Standing and maturation: Pour the mixed composite cement slurry into the mold, let it stand for 24-36 hours to further mature, and cure it at room temperature for 3-7 days to improve its strength and stability.

[0027] Preferably, in the step 2, the stirring speed of the polylactic acid and sodium alginate is 80rpm-100rpm, the stirring time of the polylactic acid and sodium alginate is 20min, the polylactic acid and sodium alginate are heated to 60-80°C during stirring to obtain a natural polymer, and the solution is gradually cooled to room temperature and then sealed and stored.

[0028] Preferably, the inorganic hydrate in step 3 further comprises the following preparation method:

[0029] S3.1. Add the weighed inorganic hydrate into the deionized water in the container;

[0030] S3.2. Use a magnetic stirrer to continuously stir to promote the dissolution of the inorganic hydrate;

[0031] S3.3. Heat the solution to no more than 60°C to accelerate the dissolution process again. After complete dissolution, allow the solution to cool naturally to room temperature.

[0032] Preferably, the ratio of the added ingredients in step 5 is calculated as:

[0033] V total =V polymer +V inorganic +V water

[0034] Among them, V waterV is the volume of deionized water to be added according to the required consistency; polymer is the volume of the natural polymer solution in mL; V inorganic is the volume of the inorganic hydrate solution in mL; V total is the volume of the main component mixture in mL.

[0035] Preferably, the viscosity adjustment calculation in step 5 is:

[0036]

[0037] Where: V cement is the volume of cement; It is the ratio of water to solid content.

[0038] Preferably, the liquidity in step 5 is calculated as:

[0039] μ final = k·(V water ) n

[0040] Among them: k and n are empirical constants obtained through experiments; μ final is the final viscosity.

[0041] Compared with the prior art, the present invention provides a composite cement and a preparation method thereof, which has the following beneficial effects:

[0042] 1. The present invention has good environmental friendliness through the ingredients of the composite cement mainly including kaolin, slag powder and limestone powder as natural minerals and wastes. Slag powder is a by-product produced in the process of steel smelting, which effectively reduces the impact of waste on the environment. The natural polymer used: a mixture of polylactic acid and sodium alginate, is derived from renewable resources, natural and biodegradable, reducing the demand for synthetic organic compounds, thereby reducing the potential pollution of organic compounds to the environment. Inorganic hydrates such as calcium sulfate and calcium hydroxide are usually substances widely present in nature. Their use further reduces the demand for organic compounds and improves the environmental friendliness of cement. Volatile organic compounds are not used in the formula of the composite cement, which avoids the release of harmful gases during the preparation and curing process and meets environmental protection requirements. Deionized water is used as a solvent to ensure that no additional minerals or pollutants are mixed into the cement, thereby improving the purity and environmental protection characteristics of the cement, and achieving the beneficial effect that the finished composite cement has environmental protection effects and does not produce organic compounds to pollute the environment.

[0043] 2. The network structure formed by polylactic acid in the cement matrix of the present invention can enhance the overall strength and slow down its degradation rate. Sodium alginate, as a natural polysaccharide, can also enhance the stability of the material. During the maturation of the finished cement slurry, the evaporation of water and the chemical reaction between cement help to form a dense structure. This dense structure makes the cement less susceptible to the influence of the external environment, thereby improving the stability of the performance. The standing and maturation steps mentioned in the preparation process can effectively improve the strength and alkali corrosion resistance of the cement by controlling the temperature, humidity and other conditions for maintenance, thereby improving its durability and degradation resistance, achieving the beneficial effect of more stable performance and not easily degraded. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic diagram of the steps of the present invention. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] See also Figure 1 , a composite cement, the composite cement is prepared by mixing a main component and a composite component, the main component is:

[0047] Kaolin 15%-30%;

[0048] Slag powder 20%-40%;

[0049] Limestone powder 10%-20%;

[0050] The compound ingredients are:

[0051] Natural polymer 5%-10%;

[0052] Inorganic hydrate 5%-20%;

[0053] The rest is deionized water;

[0054] The natural polymer is prepared by mixing polylactic acid and sodium alginate, the mass ratio of polylactic acid and sodium alginate is 1:1, and the inorganic hydrate is prepared by mixing one or two of calcium sulfate, calcium hydroxide, calcium chloride and aluminum sulfate.

[0055] The network structure formed by polylactic acid in the cement matrix can enhance the overall strength and slow down its degradation rate. Sodium alginate, as a natural polysaccharide, can also enhance the stability of the material. During the maturation of the finished cement slurry, the evaporation of water and the chemical reaction between cement help to form a dense structure. This dense structure makes the cement less susceptible to the influence of the external environment, thereby improving the stability of its performance. The standing and maturation steps mentioned in the preparation process can effectively improve the strength and alkali corrosion resistance of the cement by controlling temperature, humidity and other conditions for maintenance, thereby improving its durability and anti-degradation ability.

[0056] Specifically, cement is prepared by mixing a main component and a compound component, wherein the main component is: 30% kaolin; 40% slag powder; 10% limestone powder; the compound component is: 5% natural polymer; 5% inorganic hydrate; and 10% deionized water.

[0057] Specifically, cement is prepared by mixing a main component and a compound component, wherein the main component is: 15% kaolin; 20% slag powder; 20% limestone powder; the compound component is: 10% natural polymer; 20% inorganic hydrate; and 15% ion water.

[0058] Specifically, cement is prepared by mixing a main component and a compound component, wherein the main component is: 20% kaolin; 35% slag powder; 15% limestone powder; the compound component is: 5% natural polymer; 15% inorganic hydrate; and 10% deionized water.

[0059] A method for preparing composite cement, the preparation method comprising the following steps:

[0060] Step 1: prepare the required main components: kaolin, slag powder and limestone powder, polylactic acid, sodium alginate, inorganic hydrate, and select calcium sulfate, calcium hydroxide, calcium chloride or aluminum sulfate as needed;

[0061] Step 2: Mixing natural polymers: Mix polylactic acid and sodium alginate in a mass ratio of 1:1, and stir evenly until a uniform natural polymer solution is formed;

[0062] Step 3, preparing inorganic hydrate: selecting corresponding inorganic hydrate according to the formula: calcium sulfate, calcium hydroxide, calcium chloride, aluminum sulfate; mixing the selected inorganic hydrate with deionized water, stirring evenly until completely dissolved;

[0063] Step 4: Mix the main ingredients: In a mixing container, add kaolin, slag powder and limestone powder according to the proportion and stir well;

[0064] Step 5. Add compounding ingredients: Add the natural polymer solution prepared in step 2 and the inorganic hydrate solution prepared in step 3 to the main component mixture in proportion, continue stirring to ensure that all ingredients are evenly mixed, and add water to adjust: according to the desired final cement slurry consistency, add an appropriate amount of deionized water and stir evenly until the desired fluidity is achieved.

[0065] Step 6. Standing and maturation: Pour the mixed composite cement slurry into the mold, let it stand for 24-36 hours to further mature, and cure it at room temperature for 3-7 days to improve its strength and stability.

[0066] The ingredients of compound cement mainly include kaolin, slag powder and limestone powder, which are natural minerals and wastes, and have good environmental friendliness. Slag powder is a by-product produced in the process of steel smelting, which effectively reduces the impact of waste on the environment. The natural polymer used: a mixture of polylactic acid and sodium alginate, is derived from renewable resources, natural and biodegradable, reducing the demand for synthetic organic compounds, thereby reducing the potential pollution of organic compounds to the environment. Inorganic hydrates such as calcium sulfate and calcium hydroxide are usually substances widely present in nature. Their use further reduces the demand for organic compounds and improves the environmental friendliness of cement.

[0067] Specifically, in step 2, the stirring speed of polylactic acid and sodium alginate is 80rpm-100rpm, the stirring time of polylactic acid and sodium alginate is 20min, the polylactic acid and sodium alginate are heated to 60-80°C during stirring to obtain a natural polymer, and the solution is gradually cooled to room temperature and then sealed for storage.

[0068] A stirring speed of 80rpm-100rpm can ensure that polylactic acid and sodium alginate are fully mixed to form a uniform solution. This helps to improve the dispersion and compatibility of the polymer, thereby improving the performance of the final cement.

[0069] Improved solubility: Under heating conditions of 60-80°C, the solubility of polylactic acid and sodium alginate is significantly improved, causing the polymer to dissolve faster and more thoroughly. This high temperature environment helps break the hydrogen bonds and other interactions between molecules, making it easier for the polymer chains to unfold, thus forming a uniform polymer solution.

[0070] Enhanced physical properties: Through heating and stirring, the molecular chains of polylactic acid and sodium alginate can undergo certain physical changes, which may enhance their viscosity and fluidity, thereby improving the construction performance and final mechanical properties of the cement paste.

[0071] Promoting chemical reactions: During the heating process, the interaction between polylactic acid and sodium alginate may promote certain chemical reactions and form a more stable polymer network structure, thereby improving the strength and stability of the final product.

[0072] Specifically, the inorganic hydrate in step 3 also includes the following preparation method:

[0073] S3.1. Add the weighed inorganic hydrate into the deionized water in the container;

[0074] S3.2. Use a magnetic stirrer to continuously stir to promote the dissolution of the inorganic hydrate;

[0075] S3.3. Heat the solution to no more than 60°C to accelerate the dissolution process again. After complete dissolution, allow the solution to cool naturally to room temperature.

[0076] Specifically, the proportion of the added ingredients in step 5 is calculated as:

[0077] V total =V polymer +V inorganic +V water

[0078] Among them, V water V is the volume of deionized water to be added according to the required consistency; polymer is the volume of the natural polymer solution in mL; V inorganic is the volume of the inorganic hydrate solution in mL; V total is the volume of the main component mixture in mL.

[0079] Specifically, the viscosity adjustment calculation in step 5 is:

[0080]

[0081] Where: V cement is the volume of cement; It is the ratio of water to solid content.

[0082] Specifically, the liquidity calculation in step 5 is:

[0083] μ final = k·(V water ) n

[0084] Among them: k and n are empirical constants obtained through experiments; μ final is the final viscosity.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A composite cement, characterized in that: The composite cement is prepared by mixing a main component and a composite component, wherein the main component is: Kaolin 15%-30%; Slag powder 20%-40%; Limestone powder 10%-20%; The compound ingredients are: Natural polymer 5%-10%; Inorganic hydrate 5%-20%; The rest is deionized water; The natural polymer is prepared by mixing polylactic acid and sodium alginate, the mass ratio of the polylactic acid and sodium alginate is 1:1, and the inorganic hydrate is prepared by mixing one or two of calcium sulfate, calcium hydroxide, calcium chloride and aluminum sulfate.

2. A composite cement according to claim 1, characterized in that: The cement is prepared by mixing a main component and a compound component. The main component is 30% kaolin, 40% slag powder, and 10% limestone powder. The compound component is 5% natural polymer, 5% inorganic hydrate, and 10% deionized water.

3. A composite cement according to claim 1, characterized in that: The cement is prepared by mixing a main component and a compound component, wherein the main component is: 15% kaolin; 20% slag powder; 20% limestone powder; the compound component is: 10% natural polymer; 20% inorganic hydrate; Ionized water 15%.

4. A composite cement according to claim 1, characterized in that: The cement is prepared by mixing a main component and a compound component. The main component is 20% kaolin, 35% slag powder, and 15% limestone powder. The compound component is 5% natural polymer, 15% inorganic hydrate, and 10% deionized water.

5. A method for preparing composite cement, characterized in that: The preparation method is used to prepare the composite cement according to claim 1, and the preparation method consists of the following steps: Step 1: prepare the required main components: kaolin, slag powder and limestone powder, polylactic acid, sodium alginate, inorganic hydrate, and select calcium sulfate, calcium hydroxide, calcium chloride or aluminum sulfate as needed; Step 2: Mixing natural polymers: Mix polylactic acid and sodium alginate in a mass ratio of 1:1, and stir evenly until a uniform natural polymer solution is formed; Step 3, preparing inorganic hydrate: selecting corresponding inorganic hydrate according to the formula: calcium sulfate, calcium hydroxide, calcium chloride, aluminum sulfate; mixing the selected inorganic hydrate with deionized water, stirring evenly until completely dissolved; Step 4: Mix the main ingredients: In a mixing container, add kaolin, slag powder and limestone powder according to the proportion and stir well; Step 5. Add compounding ingredients: Add the natural polymer solution prepared in step 2 and the inorganic hydrate solution prepared in step 3 to the main component mixture in proportion, continue stirring to ensure that all ingredients are evenly mixed, and add water to adjust: according to the desired final cement slurry consistency, add an appropriate amount of deionized water and stir evenly until the desired fluidity is achieved. Step 6. Standing and maturation: Pour the mixed composite cement slurry into the mold, let it stand for 24-36 hours to further mature, and cure it at room temperature for 3-7 days to improve its strength and stability.

6. A method for preparing composite cement according to claim 5, characterized in that: In the step 2, the stirring speed of polylactic acid and sodium alginate is 80rpm-100rpm, and the stirring time of polylactic acid and sodium alginate is 20min. During stirring, polylactic acid and sodium alginate are heated to 60-80°C to obtain a natural polymer, and the solution is gradually cooled to room temperature and then sealed for storage.

7. A method for preparing composite cement according to claim 5, characterized in that: The inorganic hydrate in step 3 also includes the following preparation method: S3.

1. Add the weighed inorganic hydrate into the deionized water in the container; S3.

2. Use a magnetic stirrer to continuously stir to promote the dissolution of the inorganic hydrate; S3.

3. Heat the solution to no more than 60°C to accelerate the dissolution process again. After complete dissolution, allow the solution to cool naturally to room temperature.

8. A method for preparing composite cement according to claim 5, characterized in that: The proportion of the added ingredients in step 5 is calculated as follows: V total =V polymer +V inorganic +V water Among them, V water V is the volume of deionized water to be added according to the required consistency; polymer is the volume of the natural polymer solution in mL; V inorganic is the volume of the inorganic hydrate solution in mL; V total is the volume of the main component mixture in mL.

9. A method for preparing composite cement according to claim 8, characterized in that: The viscosity adjustment calculation in step 5 is: Where: V cement is the volume of cement; It is the ratio of water to solid content.

10. A method for preparing composite cement according to claim 9, characterized in that: The liquidity calculation in step 5 is: μ final =k·(V water ) n Among them: k and n are empirical constants obtained through experiments; μ final is the final viscosity.

Citation Information

Patent Citations

  • High-performance compound cement retarder and preparation method thereof

    CN111943563A